2016
DOI: 10.1186/s13006-017-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Have policy responses in Nigeria resulted in improvements in infant and young child feeding practices in Nigeria?

Abstract: BackgroundNigeria initiated a range of programs and policies (from 1992 to 2005) to improve infant and young child feeding (IYCF) practices. However, the prevalence of children fed in accordance with IYCF recommendations in Nigeria remains low. This paper presents time trends in IYCF practices in Nigeria for the period (1999–2013), and considers trends in the context of key national policy responses and initiatives.MethodsPrevalence and percentage change (including 95% confidence intervals) of IYCF indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…In Nigeria, for instance about 65% of newly born babies had to wait for more than an hour before they were put to breastmilk. Our findings on patterns of breastfeeding are in line with Ogbo. et al (2017) who observed that many babies born in Nigeria were denied breastmilk more than an hour after they were born.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Nigeria, for instance about 65% of newly born babies had to wait for more than an hour before they were put to breastmilk. Our findings on patterns of breastfeeding are in line with Ogbo. et al (2017) who observed that many babies born in Nigeria were denied breastmilk more than an hour after they were born.…”
Section: Discussionsupporting
confidence: 91%
“…More so, there are also no multilevel studies addressing optimal breastfeeding practices within the West African region rather contemporary studies on breastfeeding practices have mainly analysed individual factors (Genetue et al, 2017;Horii et al, 2017;Mogre et al, 2016;Ogbo. et al, 2017) as correlates of exclusive breastfeeding practice or timing of initiation of breastfeeding practices.…”
Section: Introductionmentioning
confidence: 99%
“…This can, in turn, allow unlimited time for nonworking rural women to breastfed their babies exclusively. Most working nursing mothers reside in urban areas, and labour law concerning maternity leave duration in most ECOWAS countries remains a serious challenge for promotion, protection, and support of EBF practice [13,39]. Fewer than six months of maternity leave are granted to nursing mothers in many ECOWAS countries; for example, in Ghana (12 weeks) [40], Nigeria (16 weeks) [39], and Senegal (14 weeks) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous evidence showing the benefits of EBF for the mother-infant pair [1,4,11], EBF has remained low across ECOWAS countries and varies widely between and within countries [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, Lambert and Van der Stuyft argued that the failed health care system should be blamed and not the patient because there is limited evidence to indicate that health education about TB could reduce treatment delays [49]. Improving timely diagnosis and treatment of TB in Nigeria will require improved human resources, better coordination and decentralisation of TB control programmes [6], as well as increased and monitoring of public health financing [50]. …”
Section: Discussionmentioning
confidence: 99%